Synthesis of 1,3-dihydro-5-substituted-3-[[4-[1-(p-sulphamylphenylimino) ethyl] phenyl] imino]-2H-indol-2-ones and Their in vitro Antibacterial Screening - Gupta, M.M.; Raman, S.; Srivastava, S.N. (Asian Journal of Chemistry, 2016)
A number of title compounds (4-15) have been synthesised by treating 3-[(4-acetylphenyl) imino]-1,3-dihydro-5-substituted-2H-indol-2-one (1-3) with various sulphonamide bases. The in vitro antibacterial properties of these compounds against S. aureus and B. subtilis were evaluated and some of these were found to exhibit marked activity.